Website User Interface Design Using Data Mining Task Centered System Design Method At National Private Humanitarian Institutions - Dendy K. Pramudito; Tanti Widia Nurdiani; Bambang Winardi; Arief Yanto Rukmana; Kraugusteeliana Kraugusteeliana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Humanitarian organizations that support social communities by providing work opportunities for employees. In actuality, a website is required to serve as a channel for contacting new contributors and publicizing the organization. In order to create websites for humanitarian organizations using the task-centered system design methodology, research was done based on these issues. Identification, requirements, design as a scenario, and walkthrough evaluation are the four stages of this process. The PACT framework is used to identify users and necessary tasks during the identification phase. The tasks that are actually required are then chosen at the requirements stage. The task-based design is then completed using the Figma program during the design as scenario stage. The workflow and usability of the website, which was developed utilizing cognitive walkthrough and SUS, are also evaluated at this point. Based on the findings of the assessment, it can be said that cognitive walkthrough testing can be used to assess the components of an interface that are easy to learn, effective, and efficient, and that SUS can be used to assess the usability of the design outcomes. Based on the findings of the cognitive testing, a learnability and effectiveness score of 95% with the predicate